2008
DOI: 10.3174/ajnr.a0865
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Brain MR Imaging Features Focusing on the Brain Stem and Cerebellum in Patients with Myoclonic Epilepsy with Ragged-Red Fibers due to Mitochondrial A8344G Mutation

Abstract: SUMMARY:We report 3 patients with myoclonic epilepsy with ragged-red fibers (MERRF) diagnosed by mitochondrial A8344G mutation. Cerebellar ataxia was the first symptom in all patients. Conventional brain MR imaging showed atrophy of the superior cerebellar peduncles and the cerebellum in all patients and brain stem atrophy in 2 patients. In diffusion tensor analysis, fractional anisotropy of the superior cerebellar peduncles was mildly decreased in 1 patient. There was a discrepancy between clinical disabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 10 publications
2
19
0
2
Order By: Relevance
“…Of note, although seizures are observed in both conditions as a sign of encephalopathy [7], our patient did not show signs of the pathognomonic stroke-like episodes. While no specific brain imaging features could be defined for MERRF, the basal ganglia lesions in our patient fit to the changes regularly described for this condition; cerebellar or brain stem changes which have been reported as well were not present in our patient [6]. This goes in line with the lack of ataxic or cerebellar symptoms in our patient, although a clear correlation of radiological and clinical expression cannot be assumed.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, although seizures are observed in both conditions as a sign of encephalopathy [7], our patient did not show signs of the pathognomonic stroke-like episodes. While no specific brain imaging features could be defined for MERRF, the basal ganglia lesions in our patient fit to the changes regularly described for this condition; cerebellar or brain stem changes which have been reported as well were not present in our patient [6]. This goes in line with the lack of ataxic or cerebellar symptoms in our patient, although a clear correlation of radiological and clinical expression cannot be assumed.…”
Section: Discussionsupporting
confidence: 88%
“…The presence of manifestation cerebellar ataxia is an important indicator in patients with MERRF, although it may not be present in the early phase of the disease 27,34 . However, clinical and radiological findings in patients with MERRF vary and may suggest spinocerebellar degeneration, especially in early phase of the disease 36 . Similarly, atrophy of the superior cerebellar peduncle and cerebellum, in addition to changes in the brain and basal ganglia, suggest MERRF, especially in patients with a dissociation between clinical manifestation with severe cerebellar symptoms and radiological manifestation with mild abnormalities 36 .…”
Section: What Are the Clinical Features?mentioning
confidence: 99%
“…Conventional imaging studies of the brain, such as computed tomography or magnetic resonance imaging, have confirmed that the gray matter is altered early on in patients with MERRF, while changes in the white matter can be seen more often in the later stages of the disease and are never an isolated finding 37,38 . Cerebral, cerebellar and brainstem atrophy occurs as a result of progressive neuronal loss 4,36,39 . Thus, one expects to find in patients with MERRF frequent cortical atrophy, predominantly in the brain and cerebellum, and discrete changes in the inferior olivary nucleus, cerebellar dentate nucleus, red nucleus and pons of the brainstem.…”
Section: What Are the Imaging Features?mentioning
confidence: 99%
“…Patients with myoclonic epilepsy with ragged red fi bre (MERRF) syndrome, due to the m.8344A>G point mutation, show atrophic middle pons, cerebellar hemispheres, and middle and superior cerebellar peduncles [ 103 ]. Moreover, patients with the neuropathy, ataxia, and retinitis pigmentosa (NARP) syndrome exhibit generalized pontocerebellar atrophy [ 104 ].…”
Section: Mechanisms Of Neuronal Loss In Primary Mitochondrial Diseasementioning
confidence: 99%